Pengaruh perendaman larutan basa sabun cair pencuci piring terhadap pewarnaan indigosol pada kain mori primissima - Khamidah, Khamanda Nur; Maghfiroh, Maghfiroh; Lestari, Rizki (Canting : Jurnal Batik Indonesia, 2024)
In making batik using indigosol dye, an oxidation/fixation process is required with the addition of HCl or sunlight. HCl can have an adverse effect on fabric. Therefore, alternative chemicals are used in this process using dishwashing soap. This study aims to determine the effect of soaking in dish soap on the indigosol dyeing process. The variables in this study are the results of dyeing batik cloth with dye from indigosol and fixation using sodium nitrite and HCL. The level of success is indicated by the level of fabric fragility. This research uses an experimental research method. An experimental research method is a method that aims to test the influence of a variable on another variable or test the causal relationship between one variable and another. The experimental method used in this research is a pure experimental method (true experimental). namely experiments that most closely follow procedures and fulfill experimental requirements, especially those relating to controlling variables, control groups, providing treatment or manipulating activities and testing results. The results of this research are that dishwashing soap solution can be used as an alternative acid neutralizerthat does not damage the color of the fabric.